The Analysis of English Course Book for Tenth Grade of Senior High School Based on Merdeka Curriculum - Wahyudin, Wahyudin; Novari, Ari Fajria; Rohimajaya, Nur Azmi (2025)
The research aims to analyze English textbooks Work in Progress. Based on the Independent Curriculum, there are many references for achievements learning that refers to six elements of English skills, namely listening, speaking, reading, viewing, writing and presenting in an integrated manner. The data analysis in this research was carried out by selecting data and presenting it isdata, interpret data, and draw conclusions. Data is evaluated with using the categories high, low, and null. Analysis is carried out based on chapters where this textbook has six chapters. Results of this research shows that in general the English book